Protein C and comparative biochemical changes in dogs treated with percutaneous transvenous coil embolization of congenital intrahepatic portosystemic shunts. Issue 1 (1st October 2021) - Sunlight, Crystal; Weisse, Chick; Berent, Allyson; Tozier, Eric
Abstract: Objective: To evaluate protein C (PC) activity after intrahepatic portosystemic shunt (IHPSS) percutaneous transvenous coil embolization (PTCE) in dogs; to identify if PC is associated with clinical status after intervention, and to compare PC with standard biochemical values. Study design: Retrospective case series. Animals: Forty‐seven client‐owned dogs with IHPSS undergoing PTCE. Methods: Records were reviewed for preoperative and postoperative PC, hematocrit (HCT), mean corpuscular volume (MCV), albumin (ALB), and blood urea nitrogen (BUN). Ultimate clinical status was classified as excellent, fair, or poor, based on ongoing medical management and the presence of clinical signs. Intrahepatic portosystemic shunt was considered to be completely or incompletely occluded intraoperatively based on angiography. Results: Postoperative PC activity increased in 37/47 (78.7%) dogs with a mean increase of 38.7% ± 2.1%. Ultimate postoperative clinical status was excellent in 16/43 (37.2%), fair in 19/43 (44.2%), and poor in 8/43 dogs (18.6%). No association was detected between preoperative PC (46.8% ± 1.8%) and ultimate clinical status but mean postoperative PC (75.7% ± 1.4%), HCT, MCV, ALB, and BUN were higher in dogs with excellent clinical status. Postoperative PC activity was higher when shunts were completely occluded (96.3% ± 10.9%), which was a finding associated with excellent status. Conclusion: Postoperative, but not preoperative, PC activity was higher in dogs with better ultimate clinical status. Similar trends were noted in standard hematological and biochemical values. Complete occlusion of shunts was associated with a higher postoperative PC and superior ultimate clinical status. Clinical significance: Postoperative PC may provide valuable information about the success of PTCE for IHPSS as it relates to the ultimate status and the need for additional procedures.